Kajian Pola Operasi Jalur Ganda Kereta Api Muara Enim - Lahat - Setiawan M, Dian (Universitas Muhammadiyah Yogyakarta, 2016)
Muara Enim – Lahat railway double track construction can optimise the passenger and freight transportation in South Sumatera. The objective of this study is to conduct railway double track operation concept analysis in order to obtain full concept of railway operation on this line. The result of this study become so important since it can be used for maintaining the optimisation steps of railway double track operation between Muara Enim – Lahat. This research was conducted by doing field survey and instantional survey to obtain primary and secondary data that is used as basic analysis of Muara Enim – Lahat railway track line operation. The key points included on this railway operation concept analysis are number of train per day, train length, maximum speed, station location, station function, station category, station type and activity, line capacity, and station layout.